DETERMINAN PENYERAPAN TENAGA KERJA SEKTOR PARIWISATA KABUPATEN/KOTA PROVINSI JAWA BARAT - Wardhana, Adhitya; Kharisma, Bayu; Triaryanti, Citra (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.09.NO.10.TAHUN 2020DO - 10.24843/EEB.2020.v09.i10.p05, 2020)
The aims of this study will discuss the determinants of labor absorption, namely the number of tourists, the minimum wage, the number of hotel rooms and the tourism output (PDRB) in West Java. This research uses descriptive and quantitative analysis of the regencies / cities in West Java Province. The scope of this research is as many as 25 districts / cities in West Java with the 2013-2017 period in the form of panel data. The research model used is the Generalized Least Square model. The results of this study indicate that the number of tourists, the minimum wage and the number of hotel rooms have a significant effect on employment in the tourism sector. Local governments in West Java need to carry out promotional activities or market tourism objects in the Regency / City of West Java Province so that tourism demand increases which has an impact on increasing employment in the tourism sector. It is necessary to develop the tourism sector by creating new jobs so that they can absorb human resources around the tourist destination environment. In addition, the government needs to evaluate the district / city minimum wages in West Java in order to meet the standard of decent living needs. The development of minimum wages will affect labor productivity in the tourism and non-tourism sectors.